Ginger and Warm Water Compress Reduce Complaints of Lower Back Pain in the Elderly in Gaura Village, West Sumba District, Indonesia - Januar Rizqi; Christina L. Ammakiw; Nazwar Hamdani Rahil; Agustinus Nunu; Melanie Reboldera Adolfo (Jurnal Keperawatan Respati Yogyakarta, 2023)
Low back pain is among the most frequent causes of discomfort in older adults. Non-pharmacological treatments for patients with low back pain include ginger and heated compresses, which provide a warming sensation and dilate blood vessels to alleviate pain. Objective: to compare the efficacy of ginger and tepid compresses on complaints of lower back pain among older people in Gaura Village, the Gaura Health Center's service area. This study employs a quasi-experimental design with a pre-and post-test. The population of this survey consisted of over-60-year-old residents of Gaura Village, with 17 participants in each group. The sampling technique used consecutive sampling. Independent t-test analysis of the differences between the two variables. The average lower back pain scale before the ginger compress was 6.82, while it was 6.12 before the heated compress. Ginger compression yields an average of 3.82, while mild compression yields 3.82. Ginger compresses alleviate low back pain in older people in Gaura Village, the Gaura Health Center's service area (p-value = 0.000). Warm compresses help lower back discomfort in elderly residents of Gaura Village, where the Gaura Health Center is located (p-value = 0.000). -value 0.167. Ginger and warm compresses can alleviate lower back discomfort in older people in Gaura Village, where the Gaura Health Center is located.